Pengembangan Model Soal HOTS IPA Tema 1 Alat Gerak dan Fungsinya Kelas 5 di SDN Pondok Bahar 3 Kota Tangerang - Magdalena, Ina; Safitri, Laura Amalya; Setiawan, Rangga Rizky (ANWARUL, 2023)
In the 2013 curriculum it is emphasized that students are required to be able to think critically not only understand theory and memorize. Teachers must be able to develop and convert from learning that is still a Lower Order Thinking Skill (LOTS) into a Higher Order Thinking Skill (HOTS). The type of research used in this research is descriptive quantitative. Descriptive research does not aim to find out the relationship between different variables. This study has only one independent variable by determining a saturated sample, namely making the entire population as a sample. The sample in this study were fifth grade students at SD N Pondok Bahar 3 Tangerang City, totaling 60 students. The results of the data analysis that was carried out at Pondok Bahar 3 Elementary School, Tangerang City, showed that 60 grade V students had the ability to think at a high level, namely using the HOTS question development model, which was considered quite good. The results obtained show that students who have a high HOTS level are 13 students or 21.6%, a good HOTS level is 20 students or 33.30%, an adequate HOTS level is 17 students or 28.30% and a low HOTS level is 10 students. or 16.60%.